MODEL KEPUASAN PELANGGAN: ANALISIS KUALITAS PRODUK DAN KUALITAS LAYANAN TERHADAP CITRA MEREK PADA GIANT CITRA RAYA JAKARTA - M, Agussalim; Ali, Hapzi (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2017)
This study aims to analyze the effect of product quality and service quality on brand image and customer satisfaction either partially or simultaneously on Giant Citra Raya Tangerang. The population of this study is Giant Citra Raya customers which averages 2,070,823 / 12/30 = 5752 per day. The sample in this research using Slovin formula is 152 customers. Quantitative analysis method using path analysis, followed by determination analysis (R Square), partial hypothesis testing (t test) and simultaneous (F test) with alpha 5 percent. Before further analyzed first tested the instrument and test the classical assumption. Analytical tool using SPSS version 21.0 for windows. The result of the research shows that product quality and service quality are partially and simultaneously have positive and significant effect on brand image and customer satisfaction, and brand image has influence to customer satisfaction at Giant Citra Raya Tangerang.